2017
DOI: 10.12800/ccd.v12i36.950
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a proposal for training in gender in Physical Education among students of Physical Activity and Sport Science Studies

Abstract: ResumenLa inclusión de la perspectiva de género en la formación del profesorado de Educación Física (EF) continúa siendo muy limitada en la formación inicial de los estudios de Grado de Ciencias de la Actividad Física y el Deporte (CCAFD). Dentro de este contexto, este trabajo evalúa una experiencia formativa sobre género y EF impartida a estudiantes de CCAFD de una universidad española. Un total de 53 estudiantes participaron en las dos ediciones de la formación, que fue evaluada a través de una metodología m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
(27 reference statements)
0
1
0
1
Order By: Relevance
“…Although the participants largely insisted that used inclusive language, it cannot be ignored that there were also voices that considered that this was not necessary and that the masculine gender does not make women invisible. These results seem to contradict those in other research that has focused on students' perceptions (Pastor-Vicedo et al, 2019;Camacho-Miñano & Girela-Rejón, 2017). In addition, recent qualitative research conducted by Lleixà, Soler and Serra (2020) showed that female PE students perceived lower demands and different feedback compared with males.…”
Section: Discussionmentioning
confidence: 58%
“…Although the participants largely insisted that used inclusive language, it cannot be ignored that there were also voices that considered that this was not necessary and that the masculine gender does not make women invisible. These results seem to contradict those in other research that has focused on students' perceptions (Pastor-Vicedo et al, 2019;Camacho-Miñano & Girela-Rejón, 2017). In addition, recent qualitative research conducted by Lleixà, Soler and Serra (2020) showed that female PE students perceived lower demands and different feedback compared with males.…”
Section: Discussionmentioning
confidence: 58%
“…Characteristics of group 2 of the studies found through the search process described [25,[39][40][41][42][43][44]. Group two examines teaching work and the training future teachers receive during physical activity degrees and master's degrees in teaching.…”
Section: Gender Contents In Teacher Training For Physical Educationmentioning
confidence: 99%
“…Fernández and Piedra [39], Prat-Grau and Flintoff [41], and Piedra et al [41] studied the effect of university training on attitudes and strategies future teachers apply to gender equality. Camacho-Miñano and Girela-Rejón [43] and Hortiguela and Hernando [44] devised strategies to improve this training, which was previously evaluated by the authors mentioned. Lastly, Piedra et al [25] researched what attitudes teachers had towards equality measures proposed by other authors.…”
Section: Gender Contents In Teacher Training For Physical Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…A pesar de ello, el profesorado recibe muy poca información en relación al género en su formación inicial y permanente (Camacho-Miñano & Girela-Rejón, 2017;Lleixà et al, 2020) y, cuando recibe formación, es para aprender cómo perpetuar una EF estereotipada (Flintoff & Scraton, 2006). Esto conduce a situaciones de clara discriminación hacia las alumnas (Sánchez-Hernández et al, 2019), aunque sea sin darse cuenta.…”
Section: Introductionunclassified